Educational Perspective From the Perspective of Islamic Psychology in Indonesia - Nuraini; Elsa Kusuma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Education is an important part of individual and social development, and Islamic psychology offers a unique approach to understanding human psychology. In the context of Indonesia where the majority of the population is Muslim, it is important to understand how an Islamic psychological approach can help increase the effectiveness of education. This study used a qualitative research method with a descriptive-analytic approach. Data collection was carried out through a literature review of relevant theoretical and empirical sources. The results of the study show that from the perspective of Islamic psychology, education emphasizes the importance of integrating spiritual and psychological aspects in the formation of personality and individual development. Islamic psychology teaches concepts such as morals, faith and trust that can help individuals overcome challenges in the process of learning and self-development. In addition, Islamic psychology also emphasizes the importance of developing strong character, including traits such as patience, determination, and responsibility. These concepts can be applied in the Indonesian educational context to help students deal with academic pressures, increase motivation to study and develop positive attitudes towards themselves and those around them. In addition, this study identifies several challenges that may arise in the application of an Islamic psychological approach to education in Indonesia.